Analisis Kelayakan Penyajian pada Buku Teks Bahasa Arab Kelas X Madrasah Aliyah KMA 183 Tahun 2019 - Sri Wahyuni Mohamad; Muhammad Nur Iman (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2023)
This study aims to analyze the feasibility of presenting Arabic textbooks for class X Madrasah aliyah KMA 183 in 2019 printed by the Ministry of Religion. This study uses qualitative methods as research procedures with the type of library research (Library Research). The data sources in this article are divided into two, primary and secondary. The primary data source used in this study was the Arabic Language Textbook KMA 183 Year 2019 published by the Indonesian Ministry of Religion. The secondary data sources in this research are several articles that have been published and also thesis related to the topic raised by the researcher. From the results of the researcher's analysis, it can be concluded that most of the presentations on Arabic students' books for class X KMA 2013 have met the indicators of the feasibility of presenting textbooks based on the BSNP, ranging from presentation techniques, learning presentations, to complete presentations. It's just that there is one weakness in this textbook, namely that it does not include reference sources based on information and communication technology sites in the images in the discussion of the material. Keywords: Analysis, Textbook, Arabic